2008
DOI: 10.1007/s00128-008-9622-3
|View full text |Cite
|
Sign up to set email alerts
|

The Dose–Response Relationships for EROD and GST Induced by Polyaromatic Hydrocarbons in Carassius auratus

Abstract: Freshwater fish Carassius auratus were chosen as experimental animals, the hepatic biochemical responses to medium-term exposure of five PAHs were measured as ethoxyresorufin O-deethylase (EROD) activity (phase I) and glutathione S-transferase (GST) activity (phase II) to assess sub-lethal effects. The fold increases of EROD and GST activity were calculated and both increased in the order Fluoranthene \ Fluorene \ Benzo(b)fluoranthene \ Benzo (g,h,i)perylene \ Indeno(1,2,3-cd)-pyrene. The clear doseresponse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…In a recent study, a hepatic GST activity has been induced in eel, Anguilla anguilla, after 2 and 46 h waterborne naphthalene exposure (Teles et al 2003). A more recent study carried out by Lu et al (2009) demonstrated that GST induction potential of five PAHs in gold fish, Carassius auratus, increased in the order fluoranthene \ fluorine \ benzo(h)fluoranthene \ benzo(g,h,i) perylene \ indeno(1,2,3-cd)-pyrene. In the present study, only the lowest dose (1 mg/kg bw) of phenanthrene, fluoranthene and chrysene resulted in induction (up to 1.5-fold) of hepatic total GST activities (measured with the CDNB as the substrate) in Nile tilapia where as pyrene had no significant effect on this enzyme.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent study, a hepatic GST activity has been induced in eel, Anguilla anguilla, after 2 and 46 h waterborne naphthalene exposure (Teles et al 2003). A more recent study carried out by Lu et al (2009) demonstrated that GST induction potential of five PAHs in gold fish, Carassius auratus, increased in the order fluoranthene \ fluorine \ benzo(h)fluoranthene \ benzo(g,h,i) perylene \ indeno(1,2,3-cd)-pyrene. In the present study, only the lowest dose (1 mg/kg bw) of phenanthrene, fluoranthene and chrysene resulted in induction (up to 1.5-fold) of hepatic total GST activities (measured with the CDNB as the substrate) in Nile tilapia where as pyrene had no significant effect on this enzyme.…”
Section: Discussionmentioning
confidence: 95%
“…Hence these organic compounds are called as AhR agonists (Whyte et al 2000;Timme-Laragy et al 2007). In vitro studies with mammalian and piscine cell cultures and a few in vivo studies with some fish species have compared the EROD induction potency of different PAHs (Till et al 1999;Fent and Batscher 2000;Whyte et al 2000;Basu et al 2001;Behrens et al 2001;Willett et al 2001;Bosveld et al 2002;Billard et al 2004;Lu et al 2009). In general PAHs with five-or more rings are good CYP1A inducers but inconsistent information is available on EROD induction potential of PAHs containing two to four fused rings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of xenobiotic concentrations are expensive and do not supply the amount of the impact on the biological compartment (Solé et al, 2009;Schirmer et al, 2011). The recent advances in the ecotoxicology field had supplied a number of the biomarkers in organism, which can be used to estimate either exposure to chemicals or resultant effects (Handy et al, 2003;Lu et al, 2009;Ramsdorf et al, 2012). Biomarkers and bioindicators has been extensively used as proxies to determine responses at individual level to stressors, with biomarkers being more species-specific and with higher variability of responses compared to bioindicators (Schulz and MartinsJunior, 2001;Solé et al, 2010;Linde-Arias et al, 2008a, b;Barrilli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the effects of ABC transporters in fish exposed to environmental pollutants (Christine Paetzold et al, 2009;Diaz de Cerio et al, 2012). Phase I (e.g., Cyp450) and II (e.g., Gst) detoxification enzymes catalyze the reactions of xenobiotic metabolism, and the induction of phase I and II enzymes by environmental pollutants (e.g., PAHs) has been widely studied (Kopecka-Pilarczyk and Correia, 2009;Lu et al, 2009;Yeager et al, 2009). Previous studies indicated that ABC transporters could be regulated in a coordinated manner with phase I and II enzymes (Bard, 2000;Leslie et al, 2005;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%